THE ROLE OF THE SCHOOL MANAGER FOR THE EFFECTIVE INCLUSION OF STUDENTS WITH DISABILITIES IN THE REGULAR EDUCATION NETWORK - Juliane Barros Generoso, Cibele; Cristiane Barros Moreira, Érica (Revista Gênero e Interdisciplinaridade, 2023)
The present research was carried out with the intention of verifying which attributions the school manager has for the effectuation of a true inclusion of students with disabilities in the regular education network. We know that inclusion is something that can truly happen, just think about the needs of the disabled and see them like any other citizen, with their difficulties yes, but also with their capabilities and that they have the right to education and to live in society, attending schools like any other. another student. Today, the Federal Constitution and the Law of Guidelines and Bases of Education guarantee the right of these students to preferential assistance in the regular education network, with respect for their abilities and individualities. The laws say that education is everyone’s right, so it is up to the school to learn to live with differences and trace paths that actually lead to inclusion. For this to happen, a prepared and organized school is necessary, with the school manager responsible for mobilizing and influencing those involved in the teaching process, through democratic management, in which everyone feels responsible for achieving the school’s objectives, for offering quality education.